The Role of Hypertension Exercise on Blood Pressure in Hypertension Sufferers - Sriyono, Grido Handoko; Hamim, Nur; Narsih, Umi (Al Makki Health Informatics Journal, 2023)
The prevalence of hypertension in Indonesia at ages > 18 years is increasing. Hypertension sufferers who make efforts to control blood pressure are only one-fifth of all sufferers in the world. Controlling hypertension can be done by controlling risk factors, namely by eating healthy food, reducing the amount of salt in food, not consuming alcohol, not smoking, controlling stress, and doing physical activity.